METHODOLOGICAL COMPETENCES IN TEACHERS AND UNIVERSITY STUDENTS THROUGH TRAINING INSTRUCTIONS FROM THE RESEARCH INCUBATORS - Argota Pérez, George (2022)
The purpose of the study was to describe the methodological competence in teachers and university students through training instructions from the research incubators. From June to September 2021, the project of research incubators "training and training" was carried out for teachers and students of the National University "San Luis Gonzaga", Ica (Peru). The academic area of the study was Pharmacy and Biochemistry. Based on the conceptualization for methodological competences, three levels of training instructions were considered: I) identification of what to do, II) execution of what to do and III), communication of what to do. A development model was proposed that consisted of five instructions: title, introduction, objectives, measurement and proposed improvement according to the undesired situation. The students were able to complete the proposed development model, based on creative learning and team exchange together with their tutors. The development model of the research incubator showed a pedagogical strategy of evidence of methodological skills from the university teacher and contributes to the satisfaction and improvement of academic performance in students.